Immunotherapeutic effects of intratumoral nanoplexed poly I:C. Issue 1 (2nd May 2019) - Aznar, M. Angela; Planelles, Lourdes; Perez-Olivares, Mercedes; Molina, Carmen; Garasa, Saray; Etxeberría, Iñaki; Perez, Guiomar; Rodriguez, Inmaculada; Bolaños, Elixabet; Lopez-Casas, Pedro; Rodriguez-Ruiz, Maria E.; Perez-Gracia, Jose L.; et al.
Abstract : Poly I:C is a powerful immune adjuvant as a result of its agonist activities on TLR-3, MDA5 and RIG-I. BO-112 is a nanoplexed formulation of Poly I:C complexed with polyethylenimine that causes tumor cell apoptosis showing immunogenic cell death features and which upon intratumoral release results in more prominent tumor infiltration by T lymphocytes. Intratumoral treatment with BO-112 of subcutaneous tumors derived from MC38, 4 T1 and B16-F10 leads to remarkable local disease control dependent on type-1 interferon and gamma-interferon. Some degree of control of non-injected tumor lesions following BO-112 intratumoral treatment was found in mice bearing bilateral B16-OVA melanomas, an activity which was enhanced with co-treatment with systemic anti-CD137 and anti-PD-L1 mAbs. More abundant CD8 + T lymphocytes were found in B16-OVA tumor-draining lymph nodes and in the tumor microenvironment following intratumoral BO-112 treatment, with enhanced numbers of tumor antigen-specific cytotoxic T lymphocytes. Genome-wide transcriptome analyses of injected tumor lesions were consistent with a marked upregulation of the type-I interferon pathway. Inspired by these data, intratumorally delivered BO-112 is being tested in cancer patients (NCT02828098 ).